2005
DOI: 10.1079/bjn20051593
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure measured longitudinally following hip fracture compared to predictive equations: is an injury adjustment required?

Abstract: The present study measuring resting energy expenditure (REE; kJ/d) longitudinally using indirect calorimetry in six elderly women aged $70 years following surgery for hip fracture, describes changes over time (days 10, 42 and 84 post-injury) and compares measured values to those calculated from routinely applied predictive equations. REE was compared to REE predicted using the Harris Benedict and Schofield equations, with and without accounting for the theoretical increase in energy expenditure of 35 % seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…In view of the fact that the three main meals provided daily by hospital catering contained on average 8400 kJ (2000 kcal) and 80 g protein/d, mean daily energy and protein intake per patient from main meals in the present study can very roughly be estimated as < 2100 kJ and < 20 g protein/d when DI ≤ 25 %, and as < 4200 kJ and < 40 g protein/d when DI >25–50 %. Even if an additional daily intake from snacks and supplements of about 30 % is assumed, this would only result in approximately < 2700 kJ and < 26 g protein/d, and about < 5400 kJ and < 52 g protein/d, respectively, which would still be far below most patients' requirements ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that the three main meals provided daily by hospital catering contained on average 8400 kJ (2000 kcal) and 80 g protein/d, mean daily energy and protein intake per patient from main meals in the present study can very roughly be estimated as < 2100 kJ and < 20 g protein/d when DI ≤ 25 %, and as < 4200 kJ and < 40 g protein/d when DI >25–50 %. Even if an additional daily intake from snacks and supplements of about 30 % is assumed, this would only result in approximately < 2700 kJ and < 26 g protein/d, and about < 5400 kJ and < 52 g protein/d, respectively, which would still be far below most patients' requirements ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bed rest impacts on energy expenditure and, thus energy requirements. (Miller et al. , 2005b) reported that resting metabolic rate was lower in the late post‐operative period (day 10–42) compared with the early postoperative period in patients recovering from surgery for a fractured NOF.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, há estudos que sugerem que as fórmu-las podem levar a super ou subestimação do GMR, isso porque a população estudada nem sempre corresponde à população utilizada para elaboração das fórmulas (8)(9)(10)(11)(12). No Brasil, HB é a equação mais utilizada, entretanto estudos indicam que existe uma superestimação em adultos de 18 a 59 anos, especialmente em mulheres (13,14).…”
unclassified